2017
DOI: 10.1007/s13224-017-1027-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cervical Length Measured by Transvaginal Ultrasonography and Bishop Score in Predicting Response to Labor Induction

Abstract: The Bishop score was superior in predicting the response to induction as compared to the cervical length measured by transvaginal ultrasonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 7 publications
1
14
1
Order By: Relevance
“…It was mentioned in their study that a cervical length cutoff of 27 mm would be favorable for successful induction. However, the results of some studies have contrasted with our study results; Khandelwal et al found that preinduction cervical length measurement was not associated with the induction-to-delivery success rate [24]. The differences in results may be due to the different definitions of successful induction, as some studies defined successful induction as delivery within 24 h. Meanwhile, the proficiency of the use of transvaginal ultrasound by each independent examiner may contribute to the difference in results, as a measurement of cervical length at term pregnancy tends to be more difficult as the fetus's head engages.…”
Section: Discussioncontrasting
confidence: 99%
“…It was mentioned in their study that a cervical length cutoff of 27 mm would be favorable for successful induction. However, the results of some studies have contrasted with our study results; Khandelwal et al found that preinduction cervical length measurement was not associated with the induction-to-delivery success rate [24]. The differences in results may be due to the different definitions of successful induction, as some studies defined successful induction as delivery within 24 h. Meanwhile, the proficiency of the use of transvaginal ultrasound by each independent examiner may contribute to the difference in results, as a measurement of cervical length at term pregnancy tends to be more difficult as the fetus's head engages.…”
Section: Discussioncontrasting
confidence: 99%
“…17 76±0.32 cm. This was comparable with the study done by Balaji et al where 55 cases had induction-active phase interval <12 hours which had mean Bishop score 4.6±0.7 and mean cervical length 2.4±0.3cm 19. Seventyfour cases had induction delivery interval <24 hours which had mean Bishop score 4.1±1 and mean cervical length 2.5±0.4 cm.…”
supporting
confidence: 89%
“…Although the latter study considered the ability to induce active labour as the primary outcome. 2 Rane SM et al found TVS cervical length and parity were independent predictors of vaginal delivery within 24 hours; however the only indicator for induction of labour was prolonged pregnancy. 10 Tan PC et al in 2007 observed that TVS was better tolerated than Bishop Score but both are useful predictors of the need for caesarean section following induction of labour.…”
Section: Discussionmentioning
confidence: 98%